2020
DOI: 10.1177/0885328220954188
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of intra-abdominal adhesions by a hyaluronic acid gel; an experimental study in rats

Abstract: Background In 80% to 90% of the patients intra-abdominal adhesions occur after abdominal surgery, which can cause small-bowel obstruction, chronic abdominal pain, female infertility and difficulty during reoperation. A novel crosslinked hyaluronic acid gel is evaluated regarding its anti-adhesive capacities in an ischemic button model in rats. Method 51 adult, male Wistar rats from a registered breeder, received eight ischemic buttons each and were treated with hyaluronic acid gel (HA, HyaRegen©), hyaluronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
1
4
1
Order By: Relevance
“…When analyzing the uterine horns, it was not possible to determine the placement of the patch after the recovery period. One recent study 29 reported that the formation of adhesions is a rather localized process, however we do postulate that the placement of the patches must have been sufficient for it to produce a significant reduction of macroscopic adhesions.…”
Section: Discussioncontrasting
confidence: 64%
“…When analyzing the uterine horns, it was not possible to determine the placement of the patch after the recovery period. One recent study 29 reported that the formation of adhesions is a rather localized process, however we do postulate that the placement of the patches must have been sufficient for it to produce a significant reduction of macroscopic adhesions.…”
Section: Discussioncontrasting
confidence: 64%
“…Creating an animal model of abdominal adhesions with consistent, reliable and reproducible results for positive control is a major challenge. Currently, researches are ongoing to find more efficient anti-adhesion agents and components [7,13,15]. In this experimental study, anti-adhesion agents, such as mezogel, metronidazole, dextran, and contrykal, were used.…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic and minimally invasive techniques have been adopted to reduce the trauma that may occur during surgical intervention. Laparoscopic surgery is associated with less intraabdominal adhesion than classical open surgery, but postoperative adhesion still occurs in 37.7% of patients operated with laparoscopic methods [ 8 ]. Surgical technique is not sufficient to reduce postoperative adhesions and related complications.…”
Section: Discussionmentioning
confidence: 99%